Serum vascular endothelial growth factor levels as a marker of skin thickening, digital ischemia, and interstitial lung disease in systemic sclerosis - Chinnadurai Saranya; Ramamoorthy Ramesh; Mahendran Bhuvanesh; Chilukuri Balaji; Selvakumar Balameena; Sankaralingam Rajeswari (Indian Journal of Rheumatology)
Background: Vascular injury is the initial event in the pathogenesis of systemic sclerosis (SSc) and potent proangiogenic mediators such as vascular endothelial growth factor (VEGF) are overexpressed in the skin and circulation of patients with SSc. The objective of this study was to determine the serum levels of VEGF in patients with SSc and to correlate it with the severity of skin thickening, digital ischemia, and interstitial lung disease (ILD). Methods: Serum VEGF levels were measured in 55 patients with SSC who fulfilled 2013 ACR/EULAR classification criteria for scleroderma and 30 healthy age- and gender-matched controls by ELISA. All patients underwent detailed clinical examination, baseline blood investigations, chest X-ray, electrocardiogram, and pulmonary function tests. Echocardiography and high-resolution computed tomography scan of lungs were done wherever necessary. Results: Median serum VEGF in SSc patients was higher than in the controls (675 pg/ml [interquartile range (IQR): 395–920] vs. 180.5 pg/ml [IQR: 155–215], respectively; P = 0.00001). No statistically significant difference was observed between diffuse (662.5 pg/ml [IQR: 441.25–942.5]) and limited SSc (680 pg/ml [IQR: 325–850]) (P = 0.412). Serum VEGF levels correlated significantly with higher modified Rodnan skin scores (r = 0.7168) (P < 0.0001) and lower forced vital capacity (r = −0.6771) (P < 0.0001). Median VEGF levels were higher in patients with digital ischemia (digital pitted scars, digital ulcers, and gangrene) compared to those without ischemic changes (P = 0.001). Patients with ILD (n = 21) had significantly higher median VEGF levels when compared to those without ILD (n = 34) (870 pg/ml [IQR: 592.5–1000] vs. 467.5 pg/ml [IQR: 297.5–760]; P = 0.001). There was no significant difference in serum VEGF levels between early (650 pg/ml [IQR: 375–885]) and late stages (890 pg/ml [IQR: 530–1000]) of disease (P = 0.197). Conclusion: Serum VEGF levels were elevated in SSc and they correlated with the severity of skin thickening, digital ischemia, and presence of ILD.